Penatalaksanaan Fisioterapi Pada Kasus Cerebral Palsy Spastik Quadriplegi Di Yayasan Sayap Ibu Yogyakarta - Sugesti, Ellen; , Agus Widodo, S.Fis.,Ftr., M.Fis (2015)
Background: Cerebral palsy spastic quadriplegia is a brain disorder or damage to non-progressive that occur in the process of growth and development which showed the presence of symmetric interference of all four limbs, both arms and legs which is almost the same weight. Problems often arise in the form of spastic CP quadrilegia are posture disorders, motion control, balance and motor coordination that would potentially functional disruption of daily activities. Objective: To know the benefits of snoezellen, massage, and vojta therapy in reducing spasticity, relaxation and improve functional ability to cerebral palsy spastic quadriplegia. Results: after therapy 6 times showed a decrease spasm with palpation is on m.upper trapezius, decrease of spasticity as measured using a scale of Asworth was only last ± 30 menutes after therapy and for the functional capabilities with GMFM current value T0: 4.21% and at T6: 4.21% no increase to the right and left oblique. Conclusion: Snoezelen can reduce spasticity in CP spastic quadriplegia conditions, massage and merileksasikan and reduce spasm in m. Upper trapezius on CP spastic quadriplegia conditions, and vojta therapy can not improve functional ability